2022
DOI: 10.3748/wjg.v28.i45.6421
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA2 variants in advanced pancreatic acinar cell carcinoma: A case report and review of literature

Abstract: BACKGROUND Pancreatic acinar cell carcinoma (PACC) is a rare tumor. Up to 45% of PACCs have alterations in the DNA damage repair pathway and 23% harbor rearrangements in the BRAF or RAF1 genes. We present a PACC case with a germline BRCA2 likely pathogenic variant (LPV) to highlight the impact of genomic testing on treatment decisions and patient outcomes. In our larger case series, we provide clinic-based information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…There have been numerous case reports of one particular class chemotherapy drugs, Folfirinox and its predecessor Folfiri, eliciting psychotic features in patients [159][160][161][162][163][164], including mania with delusions [162] or, in some cases, triggering only visual or auditory hallucinations [165,166]. Folfirinox is a combination of folinic acid, 5-fluorouracil (5-FU), irinotecan and oxaliplatin.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Treating C...mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous case reports of one particular class chemotherapy drugs, Folfirinox and its predecessor Folfiri, eliciting psychotic features in patients [159][160][161][162][163][164], including mania with delusions [162] or, in some cases, triggering only visual or auditory hallucinations [165,166]. Folfirinox is a combination of folinic acid, 5-fluorouracil (5-FU), irinotecan and oxaliplatin.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Treating C...mentioning
confidence: 99%
“…In the case reports of Folfirinox causing psychotic symptoms, if there was attribution of the cause of the cases of psychosis, the authors have pointed towards 5-FU alone [160,165], to steroid psychosis from coadministered steroids [163] or to the cancer mechanism itself [162] without evaluating what might happen if excess folate is administered when the normal destination of methyl groups towards DNA synthesis is blocked. Rustum [174] demonstrated that modest increases in what he termed "reduced folates" occurred with 5-FU infusion alone in an animal model (Table 2 of Rustum, [174]), likely because their consumption by the DNA synthetic pathway was blocked, but massive increases in 5-methyl-THF (which is indeed one form of "reduced folate") specifically occurred with co-infusion of 5-FU and high-dose folinic acid (Table 3 of Rustum, [174]).…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Treating C...mentioning
confidence: 99%
“…Acinar cell carcinoma pancreas configures ~ 2% of adult pancreatic neoplasms and ~15% of paediatric pancreatic tumours. 1,2 Acinar cell carcinoma pancreas exhibits a mild male predilection with male to female proportion of 2.1:1. Average age of disease emergence is 60 years.…”
Section: Introductionmentioning
confidence: 99%
“…Head of pancreas configures as a frequent site of disease emergence. 1,2 Acinar cell carcinoma pancreas is posited to occur due to cellular accumulation of genetic alterations or occurrence of chromosomal instability a Acinar cell carcinoma nd frequent allelic copy number variation. 3,4 Additionally, acinar cell carcinoma is postulated to arise from factors such as tobacco consumption or cigarette smoking and defective repair of deoxy ribonucleic acid (DNA) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review found that up to 22% of ACC patients have BRCA1/2 gene defects ( 4 ). In patients with ACC harboring BRCA2 gene mutations, platinum-based chemotherapy drugs have shown particular sensitivity, and regimens such as FOLFIRINOX have achieved good results ( 3 , 5 , 6 ). In this case, thanks to the targeted therapy based on the BRCA2 germline mutation detected through genetic testing, platinum-based chemotherapy was used as neoadjuvant chemotherapy, and satisfactory results were achieved before surgery, converting the previously unresectable tumor into a potentially resectable one.…”
mentioning
confidence: 99%